Влияние P,Т-обработки на свойства монокристалла сапфира - Шульженко, А. А.; Розенберг, О. А.; Соколов, А. Н. (Eastern-European Journal of Enterprise Technologies, 2009)
The impact of thermal processing under high pressures has been studied, in different environments on the structure and properties of monocrystal sapphire